Developing of module challenge based learning in environmental material to empower the critical thinking ability - Nawawi, Sulton (Jurnal Inovasi Pendidikan IPA, 2017)
This research aimed to compile a product development, knowing the feasibility and knowing the effectiveness of challenge-based learning (CBL) modules in an environmental material to empower the critical thinking ability. The research was a research & development model of Borg & Gall. Validation the product was done by material expert, expert of development and design module, expert of device and evaluation of learning , a linguist and practitioner of learning of Biology. Subject of the research was a student of grade X MIA Islamic State Senior High School Karanganyar. This research results are: (1) module in the form of product module for teachers and students CBL based on environmental material was developed based on CBL syntax and indicators of Fascione's critical thinking that visualized in the objective, material, activities , and evaluation items; (2) appropriateness of module for teachers and student based on CBL environment material according to the validation results of qualified as good until very good; (3) Modules based CBL environmental material is effective to improve the ability of student critical thinking.